Association between anemia-related biomarkers and the adequacy of peritoneal dialysis in Chinese patients with chronic kidney disease - Jia-Lin Li; Zhen Cai; Jing Zhao; Xiang-Gang Zhu; Qian Li; Yan-Shuang Li; Meng-Chao Liu; Fang-Qiang Cui; Wen-Jing Zhao; Wen-Quan Niu (Frontiers in Physiology, 2023)
Objectives: The study aimed to examine the association of three anemia-related biomarkers with the adequacy of peritoneal dialysis (PD) in patients with chronic kidney disease (CKD).Methods: This study included 127 PD patients. The total Kt/V urea (Kt/V) was calculated according to the Kidney Disease Outcomes Quality Initiative (K/DOQI) guidelines. All patients were classified into two groups based on Kt/V, viz., adequate (Kt/V ≥1.7) and inadequate (Kt/V <1.7) groups. Effect sizes are expressed as odds ratios (ORs) and 95% confidence interval (CI).Results: After adjusting for age, gender, hypertension, diabetes, and PD duration, 20 g/L increment in hemoglobin (Hgb) was observed to significantly reduce the risk of inadequate PD by 19% (OR; 95% CI; P: 0.81; 0.70 to 0.95; 0.009), 5 g/L increment in the mean corpuscular hemoglobin concentration (MCHC) by 7% (0.93; 0.88 to 0.98; 0.009), and 5% increment in transferrin saturation (TS) by 23% (0.77; 0.64 to 0.94; 0.012). The gender-specific nomogram model was constructed by incorporating three significant anemia-related biomarkers and convenient influencing factors, and the prediction accuracy was good (concordance index (C-index): 0.686 for men and 0.825 for women).Conclusion: Our findings indicate that the deterioration of three anemia-related biomarkers (Hgb, MCHC, and TS) can precipitate the development of inadequate PD in Chinese patients with CKD.